(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Quantum computing represents a transformative technological advancement with the potential to revolutionize numerous fields, including cryptography and data security. Unlike classical computers, which process information in binary bits, quantum computers utilize quantum bits (qubits) that exploit principles of superposition and entanglement, allowing for exponentially faster computation in specific problem domains